Understanding the mechanism of change in morphological structures, visualization features, and physicochemical characteristics of adlay seeds (Coix lacryma-jobi L.): The role of heat soaking. (January 2020) - Ding, Yangyue; Zhang, Gaopeng; Ni, Chunlei; Yu, Guoping; Cheng, Jianjun; Zheng, Huanyu
Abstract: Heat soaking is an essential factor deciding the final quality of hard-to-cook grains. In this study, the morphological structures, visualization features, and physicochemical characteristics of adlay seeds soaked at 30–70 °C were investigated compared with waxy rice (easy to cook). The morphology of macromolecules and section cracks were observed by scanning electron microscopy and light microscopy as these are the crucial factors for penetrate water penetration, which showed that starch granules were slightly eroded when adlay seeds were soaked at 70 °C. The MRI images showed that at higher soaking temperatures, the moisture of soaked adlay seeds was distributed more evenly across a gradient. Meanwhile, heat soaking has a minor effect on starch and protein content of adlay seeds, and the proportion of bound water of adlay seeds slightly declined after heat soaking. Moreover, hardness analysis and pasting measurements exhibited structural changes and viscosity transition in the grains. However, the contribution of heat soaking to the infrared spectrogram and relative crystallinity of adlay seeds was insignificant. This study provides effective methods to evaluate changes in adlay seeds during heat soaking and explains why it is hard to cook. Graphical abstract: Does heat soaking of adlay seeds ( Coix lacryma-jobi L.) decide its morphological structures, visualization features, and physicochemical characteristics? Image 1 Highlights: Soaking temperature had no great influence on the micro-morphology of adlay seeds. The hardness of adlay seeds changed significantly but exhibited a non-linear trend. Moisture distribution change in a grain during soaking was visualized by MRI. The peak viscosity of adlay seed flour was increased with soaking temperature. The contribution of soaking temperatures to RC of adlay seeds is insignificant.